Response of Soil Microarthropod Community to Seasonal Changes in Urat Desert Steppe, Inner Mongolia - Guo, Zhixia; Chang, Haitao; Liu, Rentao (Frontiers in Environmental Science, 2022)
The abiotic factors via moisture and temperature play the most important role in the growth and development of soil microarthropods. Here we examined the seasonal distribution of the soil microarthropod communities in the Reaumuria soongorica shrubland of the Urat desert steppe in northwestern China in spring, summer, and autumn of 2019 and their relations with environmental factors. Our results showed that the total abundance and group richness of soil microarthropods community was significantly greater in summer than in spring and autumn. There were two indicator taxon (i.e., Cryptopalmites and Isotomidae) observed in summer, and one indicator taxon (i.e., Stigmaeidae) observed in autumn, whereas no indicator taxon was observed in spring. The partial RDA results showed that soil moisture and soil temperature were the main environmental factors that affected the distribution of soil microarthropods. In conclusion, the warm and moist summer harbored greater abundance and richness distribution of soil microhabitats, whereas there was stable diversity distribution across seasons in Urat desert steppe, northern China.